Music preferences of Malaysian students and KBSM curriculum implications - Ang, Minni K.; Yeoh, Miranda P. (Universiti Putra Malaysia Press, 2002)
Preferences were investigated of a sample of teenage students for ethnic-based and non ethnic related Malaysian music, and the effects of selected listener haracteristics: familiarity and musical training. Ten excerpts of ethnic-based Malaysian music and twenty excerpts of non ethnic-related music comprising ten popular music excerpts and ten Western art music excerpts were utilised. Ratings of preferences, familiarity, and musical training were gathered from 139 randomly selected teenage students of two public schools in Serdang. The results showed that the teenage students had a strong preference for non ethnic-related music especially popular music. Familiarity proved to be a significant determinant of preferences for both ethnic-based Malaysian music and non ethnic-related music. Implications of these findings include the proposal of new strategies in teaching approaches and preparation of learning materials for the music subject of the Malaysian Integrated Secondary School Curriculum or KBSM.